(untitled) (International Journal of Economics Management and Social Science, 2026)
Modern container and tanker vessels operate with multinational crews speaking diverse first languages, yet maritime communication remains heavily dependent on standardized English procedures and International Maritime Organization protocols. This ethnographic study examined communication practices aboard 22 commercial vessels over 20 months, combining 224 hours of bridge observation, analysis of 163 audio-recorded bridge operations, 64 semi-structured interviews, and review of 52 communication-related incident reports. Findings reveal tension between standardized English-only maritime communication protocols and practical multilingual realities aboard vessels where officers from Philippines, Eastern Europe, India, Myanmar, and other nations communicate with varying English proficiency. Quantitative analysis of bridge communications revealed that 38% of operational communications contained code-switching (mixing English with officers’ first languages), 31% included non-verbal communication elements critical for comprehension, and 44% of junior officers from non-English-speaking backgrounds requested clarification at least weekly. Qualitative analysis identified communication barriers: limited vocabulary among non-native English speakers for novel situations, cultural communication style differences (direct versus indirect, formal versus relational), psychological safety limitations preventing questions, and insufficient training in multimodal communication (combining verbal language, visual cues, technological interfaces, and body language). A curriculum pilot integrating multimodal communication pedagogy into Maritime English courses—emphasizing cultural communication style awareness, video-based analysis of effective cross-cultural maritime communication, scenario-based practice with multilingual crews, and explicit attention to psychological safety for questions—demonstrated measurable improvements: 28% increase in students’ code-switching effectiveness, 34% improvement in students’ cross-cultural comprehension, and increased reported confidence communicating with linguistically diverse crews (mean 3.1/5.0 pre-intervention to 4.2/5.0 post-intervention). Findings establish that maritime education can prepare officers for realistic multilingual communication contexts through pedagogy explicitly addressing cultural diversity and multimodal communication strategies rather than through idealized assumption of standardized English monolingualism. Keywords : Maritime communication; Multilingual communication; Intercultural communication; Bridge operations; Maritime English; Communication pedagogy; Cultural competence